PENGARUH SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN - NINGRUM, FITRIA (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out how the influence of computer based accounting information system which is implemented to the company as well as the risk which will be encountered in the future in the implementation of computer based accounting information system at CV Trias Persada Engineering, Sidoarjo.The quantitative analysis case study method is applied as the analysis instrument in this research by formulating hypothesis and then the statistic examination is performed by the researcher to accept or deny the hypothesis. The data collection technique which is conducted by the researcher is literary and field research. Field research is performed by distributing questionnaires to the respondent, while the literary research is performed by comparing the theories which are obtained from books and literatures with the existing facts. It can be concluded from the result of discussion and analysis that the users of computer based accounting information system at the company have significant influence to the making of purchasing decision at the company, although there are minor mistakes in the system but reparation will always be carried out so the accounting information system is in appropriate with the procedures and the rules in this company. Keywords: Accounting Information System, Computerization, the Making of Purchasing Decision